2020
DOI: 10.15835/nbha48111806
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming as a promising technique to improve growth, chlorophyll, photosynthesis and nutrient contents in cucumber seedlings

Abstract: Seed priming is a technique to improve seed germination, seedlings growth, uniformity and yield. The, present study was designed to, investigate the physiological mechanism of seed priming with GA3 and KNO3 on cucumber seedlings growth, chlorophyll, photosynthesis and nutrients uptake. The cucumber seeds were treated as; CK; control, T1; GA3 100 ppm, T2; GA3 200 ppm, T3; KNO3 1%, T4; KNO3 5%, before seed sowing. The results showed that seed priming with GA3 and KNO3 significantly increased the plant height, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 30 publications
11
30
2
3
Order By: Relevance
“…Whereas the seedlings of control treatments showed inferior results as compared to other osmopriming treatments. Our study is in corroboration with another study in which the increased photosynthetic rate, respiration rate and CO2 index of cucumber seedlings as the result of seed priming with KNO3 was reported (Anwar et al, 2020). Photosynthesis rate of the seedlings has a positive correlation with the growth of seedling (Anwar et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas the seedlings of control treatments showed inferior results as compared to other osmopriming treatments. Our study is in corroboration with another study in which the increased photosynthetic rate, respiration rate and CO2 index of cucumber seedlings as the result of seed priming with KNO3 was reported (Anwar et al, 2020). Photosynthesis rate of the seedlings has a positive correlation with the growth of seedling (Anwar et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Our study is in corroboration with another study in which the increased photosynthetic rate, respiration rate and CO2 index of cucumber seedlings as the result of seed priming with KNO3 was reported (Anwar et al, 2020). Photosynthesis rate of the seedlings has a positive correlation with the growth of seedling (Anwar et al, 2020). A previous study indicated that the leaf nitrogen and chlorophyll contents have a positive correlation, and can derive the photosynthesis rate being a key molecule for photosynthesis (De Castro et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Potassium maintains better water uptake across cell membranes [ 75 ]. However, the high doses of theses nutrients are toxic and adversely affecting the cellular metabolic activities [ 76 ]. In the present study, the positive effects of seed priming with low doses of CRE on different germination attributes might be due to the presence of macro- or micro-nutrients that not only reduced the seed osmotic potential for better water uptake but also affected the activities of germination enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In the other two species, the effects of priming were smaller and usually not significant, although in general, cathodic water gave the best results. Although not tested for cathodic water, priming with other solutions is well known to improve photosynthesis in the resulting seedlings [39] (for review see [38]). Theoretically, priming may have increased the capacity for photosynthetic electron transport, or possibly a greater investment in enzymes of the Calvin cycle [40].…”
Section: Effects Of Priming On Photosynthetic Parametersmentioning
confidence: 99%